2022
DOI: 10.1186/s13052-022-01337-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the covid-19 pandemic on puberty: a cross-sectional, multicenter study from Turkey

Abstract: Backgrounds During the Coronavirus-19 disease (Covid-19) pandemic it was observed that the number of girls presenting with early puberty had increased. The aim of this study was to carry out a retrospective evaluation of the characteristics of girls who had been referred for evaluation of precocious puberty in five different pediatric endocrinology units, before and during the pandemic. Methods The study participants comprised 359 girls who were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…A different study conducted among several pediatric endocrinology clinics in Turkey reported an increase in precocious puberty and significantly accelerated puberty cases during the pandemic; the need for pubertal suppression treatment with GnRH analogs was augmented too. Comparing the two groups, age at presentation and age at pubertal onset were lower in the pandemic group than those in the pre-pandemic group but there was no significant difference between the BMI SDS values of the two groups ( 61 ).…”
Section: Precocious Puberty During the Covid-19 Pandemicmentioning
confidence: 81%
“…A different study conducted among several pediatric endocrinology clinics in Turkey reported an increase in precocious puberty and significantly accelerated puberty cases during the pandemic; the need for pubertal suppression treatment with GnRH analogs was augmented too. Comparing the two groups, age at presentation and age at pubertal onset were lower in the pandemic group than those in the pre-pandemic group but there was no significant difference between the BMI SDS values of the two groups ( 61 ).…”
Section: Precocious Puberty During the Covid-19 Pandemicmentioning
confidence: 81%
“…In the published reports of increased PP during COVID-19, in 2020, the reported cases were relatively disproportionally distributed, with 678 cases in Italy[ 2 - 6 ], 275 in Turkey[ 8 - 10 ], 237 in China[ 11 ], 22 in Brazil[ 12 ] and 155 in India[ 13 ]; Portugal was not included in further analyses (see below for details). In South Korea, with data obtained from the country’s hospital records/healthcare database, 95524 children were diagnosed with PP in 2017 (9.89% boys), increasing over the years to 166645 children in 2021 (19.55% boys).…”
Section: Resultsmentioning
confidence: 99%
“…Recent publications from several countries[ 2 - 5 ] have reported that more young people[ 6 - 10 ] (mainly girls) are experiencing PP/menarche during the coronavirus disease 2019 (COVID-19) pandemic compared to the past[ 11 - 13 ]. This variation is attributed to the stress of confinement, lack of exercise, obesity, and disturbed sleep patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Many publications have been shared about the increase in puberty precocious cases from different continents of the world during the pandemic (5,(10)(11)(12)(13). This increase during the pandemic is associated with increased obesity and screen exposure due to closure and sedentary life (10).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the ages at the presentation of the patients who presented before and during the pandemic period were similar to each other. In studies in the literature, studies are showing that the ages of the cases admitted during the pandemic period were younger (11,12,20).…”
Section: Discussionmentioning
confidence: 99%